An investigation of tribochemical reaction kinetics from the perspective of tribo-oxidation. (January 2022) - Yu, Hongxiang; Zheng, Zhiwen; Chen, Haijie; Qiao, Dan; Feng, Dapeng; Gong, Zhenbin; Dong, Guojun
Abstract: The tribochemical reaction rate of multiply alkylated cyclopentane (MAC) was studied from the perspective of tribo-oxidation. The activation energy of MAC oxidation reaction and respective decrease of activation energy owing to catalysis from iron and Fe3 O4 were determined by means of auto-oxidative tests. The sum of the reduced activation energy due to iron and Fe3 O4 was less than that in tribological test, which highlighted the crucial role of shear stress in accelerating tribo-oxidation reaction. Additionally, the experimental process was replicated by utilizing reactive molecular dynamics (MD) simulations. The simulation results revealed the significance of shear stress in tribo-oxidation reaction and the catalytic mechanism of iron, Fe3 O4, and shear stress for promoting oxidation reaction was interpreted. Graphical Abstract: ga1 Highlights: The tribochemical reactions of MAC are extremely complex, including oxidation, pyrolysis, and polymerization reaction. The tribochemical reaction rate is studied from the perspective of tribo-oxidation. Decrease of activation energy in friction is determined by thermally activated, stress-assisted reaction rate model. The MD simulation results equally reveal the significance of shear stress in tribo-oxidation reaction. The catalytic mechanism of iron, Fe3O4, and shear stress for promoting oxidation is interpreted by MD simulation.